2013
DOI: 10.3389/fchem.2013.00018
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically nanostructured materials for sustainable environmental applications

Abstract: This review presents a comprehensive overview of the hierarchical nanostructured materials with either geometry or composition complexity in environmental applications. The hierarchical nanostructures offer advantages of high surface area, synergistic interactions, and multiple functionalities toward water remediation, biosensing, environmental gas sensing and monitoring as well as catalytic gas treatment. Recent advances in synthetic strategies for various hierarchical morphologies such as hollow spheres and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 204 publications
(245 reference statements)
0
52
0
Order By: Relevance
“…36 37 Surprisingly, in present case, some hierarchical APO/NFO microstructures was appeared which are formed by different combination and arrangement of dissimilar units leading to multiple functionalities and it may assists to enhance photocatalytic performance (see supporting information, Figure S3). 38,39 Such, hierarchical APO/NFO composites represent a good design that can tailor optical, mechanical and surface properties. Thus, APO/NFO composites, consisting of irregular structures with sharp corners, edges, and smooth surfaces can be fabricated without capping agents by simple precipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…36 37 Surprisingly, in present case, some hierarchical APO/NFO microstructures was appeared which are formed by different combination and arrangement of dissimilar units leading to multiple functionalities and it may assists to enhance photocatalytic performance (see supporting information, Figure S3). 38,39 Such, hierarchical APO/NFO composites represent a good design that can tailor optical, mechanical and surface properties. Thus, APO/NFO composites, consisting of irregular structures with sharp corners, edges, and smooth surfaces can be fabricated without capping agents by simple precipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical systems are drawing attention in catalysis for their multicomponent and layered systems which can give rise to enhanced performance . These hierarchical systems typically require elaborate synthetic strategies.…”
Section: Case Studiesmentioning
confidence: 99%
“…[27] Therefore, numerous strategies have been applied to lower their band gap energy such as incorporation of foreign ions, defect engineering, introducing a surface disorder layer, and forming a solid solution. Some popular strategies have been developed such as light scattering by hierarchical structures, [36] resonant light trapping/optical wave-guiding, [37] integrating with plasmonic structures, [38] and employing radiative and nonradiative energy transfer Adv. [28] Additionally, the dopants might introduce defect states within the band gap of TiO 2 , thus redshifting the active spectrum of TiO 2 .…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Because of the well-controlled environment (vacuum), PVD thin films usually have low impurity and thus high quality. [7,19,36,47,76,176,177,194,195] Wang et al reported a synthesis of highly mismatched ZnO/ZnSe core/shell NW arrays on transparent conducting substrates combining CVD of ZnO NW arrays and PLD of ZnSe shell. [187] Line-of-sight deposition is another constraint, limiting the usage of PVD for substrates with complex geometry.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%